Mutually beneficial company-community partnerships in plantation development: emerging lessons from Indonesia - Nawir, A.A.; Santoso, L. (2005)
Social conflicts with local people have caused some unsuccessful timber plantation developments in Indonesia. Company and community partnerships have provided opportunities for companies to accommodate local communities’ involvement and attempt to overcome these difficulties. Constraints in establishing mutually beneficial partnerships were studied, mainly to improve their long-term viability. The main components of a successful mutually beneficial partnership were defined as: commercial feasibility, equitable contractual agreements, the full understanding of both parties of the potential benefits and costs, and risks of joining the partnership, and a shared understanding of co-management and participatory approaches. The implementation of all three case studies suffered from: a lack of mechanisms to build trust; challenges to commercial viability due to inadequate management planning and consequently poor implementation; inadequate assessment of community needs and resulting waste of companies’ funds when developing income generating packages; no clear long-term reinvestment strategy; and poorly developed negotiation and renegotiation mechanisms.